A Review of Hypothalamic-Pituitary-Adrenal Axis Function in Chronic Fatigue Syndrome. (30th September 2013) - Tomas, Cara; Newton, Julia; Watson, Stuart
Abstract : Hypothalamic-pituitary-adrenal (HPA) axis dysfunction has been found in a high proportion of chronic fatigue syndrome (CFS) patients and includes enhanced corticosteroid-induced negative feedback, basal hypocortisolism, attenuated diurnal variation, and a reduced responsivity to challenge. A putative causal role for genetic profile, childhood trauma, and oxidative stress has been considered. In addition, the impact of gender is demonstrated by the increased frequency of HPA axis dysregulation in females. Despite the temporal relationship, it is not yet established whether the endocrine dysregulation is causal, consequent, or an epiphenomenon of the disorder. Nonetheless, given the interindividual variation in the effectiveness of existing biological and psychological treatments, the need for novel treatment strategies such as those which target the HPA axis is clear.